Beyond Kantianism - Response to Critiques - Kevin Stenson (Social Work and Society)
I am flattered and privileged to have received four such astute critiques of my work from an international cast. I will reflect at length about many of their points in future work but to respond fully would require a very long article and so I will highlight some of the more salient issues. The authors share misgivings about my commitment to a realist version of governmentality theory so I will try to articulate a bit more clearly how it is different from two major alternative perspectives highlighted by the authors: what I term a `discursive` governmentality perspective (Stenson 2005), and the neo-Marxist regulationist school of political economy. However, deeper normative questions are raised, for example by Wendy Larner, about what it means to be progressive or critical within the broad terrain of liberalism (which can include neo-liberals and neo-conservatives) in the wake of the collapse of communism and much of the power of western labour movements, the rise of the new emancipatory and environmental social movements and varieties of religious fundamentalism.